2020
DOI: 10.1155/2020/8160256
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Early Cataracts in Young Type 1 Diabetes Group: A Nationwide Cohort Study

Abstract: Background. Chronic hyperglycemia in type 1 diabetes (T1D) patients results in ocular problems over time, but only a few studies emphasized on cataracts. Aim. To evaluate the epidemiology of cataracts in the T1D population. Method. A two-part study was conducted using data from the National Health Insurance Research Database in Taiwan. Information from the Longitudinal Health Insurance Database (LHID) was served as a template of the general population. In the first part, a total of 3,622 T1D cases registered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Our finding that lens resident immune cells serve as myofibroblast progenitors strongly suggests that these cells are mediators of PCO. In addition, autoimmune pathogenesis has long been considered a factor in age‐related cataracts, as well as in the high incidence of cataracts in autoimmune diseases such as diabetes and uveitis 70‐75 . Our discovery of resident immune cells in the lens would be consistent with a role in cataractogenesis.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our finding that lens resident immune cells serve as myofibroblast progenitors strongly suggests that these cells are mediators of PCO. In addition, autoimmune pathogenesis has long been considered a factor in age‐related cataracts, as well as in the high incidence of cataracts in autoimmune diseases such as diabetes and uveitis 70‐75 . Our discovery of resident immune cells in the lens would be consistent with a role in cataractogenesis.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, autoimmune pathogenesis has long been considered a factor in age-related cataracts, as well as in the high incidence of cataracts in autoimmune diseases such as diabetes and uveitis. 70 75 Our discovery of resident immune cells in the lens would be consistent with a role in cataractogenesis. Resident immune cells provide a potential new therapeutic target to consider for both PCO and cataract.…”
Section: Discussionmentioning
confidence: 68%
“…This system has the advantage of good accessibility and consists of a total population of over 99%. The National Health Insurance Research Database (NHIRD), derived from NHI, can be analyzed for records of public health research [ 22 , 23 , 24 ]. The death registration database (which was initiated in 1997) was accessed from the NHIRD, and the age of death, cause of death (using the definition from the International Classification of Diseases [ICD]), and place of death were recorded [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…4 Several studies reported higher incidence rates for females. [4][5][6] The risk of cataract development seems to be higher in individuals with diabetes type 2 than in individuals with diabetes type 1. 7 There are data on prevalence and risk factors for retinopathy [8][9][10] in children and adolescents, but there are only scarce data about cataract formation.…”
Section: Introductionmentioning
confidence: 99%
“…In younger age groups (<55 years) the incidence rates differ most between individuals with and without diabetes, showing higher incidence rates for individuals with diabetes 4 . Several studies reported higher incidence rates for females 4–6 . The risk of cataract development seems to be higher in individuals with diabetes type 2 than in individuals with diabetes type 1 7 …”
Section: Introductionmentioning
confidence: 99%